The effect of sowing time on the yield and the variance of the seed moisture content a harvest of maize (Zea mays L.) hybrids - Molnár, Zsuzsa; Sárvári, Mihály (Acta Agraria Debreceniensis, 2006)
Sowing time is an important crop technology element of maize. We studied the effect of this factor on the growth and production of maize in an experiment carried out near Hajdúböszörmény, in 2003 and 2004, and near Debrecen, in 2005. The soils of the experiments were humic gley soil and chernozem. Weather in both years differed greatly. 2003 was drought. Neither the distribution, nor the quantity of the precipitation were suitable in the growing season for maize. This fact basically determined the results. In 2004 and in 2005, there were favorable and rainy seasons. The distribution and quantity of precipitation were suitable between April and September. The average temperature was also suitable for maize. In 2003, we tested seven hybrids at four sowing times. Hybrids with a shorter vegetation period gave the highest yield at the later sowing time, while the hybrids with a longer vegetation period gave them at the earlier sowing time. The yield of PR34B97, PR36N70, PR36M53 hybrids were the best at every sowing times. The moisture loss of hybrids in the late maturity group was faster in the maturity season, but the seed moisture content was higher than the hybrids with early sowing time. The seed moisture content was very low due to the droughty year. In two hybrid cases, this value was higher than 20% only at the fourth sowing time. In 2004, we examined the yield and seed moisture contents of nine hybrids. In the favorable crop year, the yield of every hybrid was the highest at the second and third sowing times. Yields of PR34H31 and PR38B85 hybrids were significant. The seed moisture content at harvest was higher than the previous year, due to the rainy season. In the case of hybrids sown later, this value was higher by 30%. However, we noticed that this value was lower at the earlier sowing time, than at the later. In 2005, we applied three sowing times. Unfortunately, the results of the third sowing time could not be analyzed, due to the low plant density. The yield of the six hybrids varied from 12 to 14 t/ha at the first sowing time. At the second sowing time, the yields fluctuated and each hybrid had the lowest yield, except the PR37D25 hybrid. At the latest sowing time, the yield of the PR34B97 hybrid was the lowest. However, this low yield was due to damage from the Western corn rootworm (Diabrotica virgifera) imago. The moisture content at harvest of the hybrids varied from 16 to 24% at the first sowing time. Yields at the second sowing time were higher. The low yield of the PR34B97 hybrid coupled with a higher seed moisture content. In addition, the maximum value of the LAI was more favourable at the first sowing time, and ranged between 5-5.5 m2/m2. The crop year had a more dynamic effect on maize than the sowing time. First of all, the quantity and distribution of precipitation played an important role in respect to yield safety.